ASSESSING THE IMPACT OF MOBILE-ASSISTED LANGUAGE LEARNING (MALL) APPS ON VOCABULARY ACQUISITION (Eureka Journal of Computing Science & Digital Innovation, 2026)
The effectiveness of Mobile-Assisted Language Learning (MALL) for learning English vocabulary among Chinese college students using the Word Learning-CET4 mobile application is explored in this research. A quasi-experiment design is used in this study, and two classes are assigned to each group in this research. The experimental group is composed of students learning English vocabulary using the mobile application, and the control group is composed of students learning English vocabulary using traditional learning processes. A two-way ANOVA is used in this study to analyze the results obtained from the post-test. The results show that the experimental group outperformed the control group in learning English vocabulary by approximately 8.49% when compared to the average post-test scores. The use of mobile applications to facilitate learning and training in learning English vocabulary is crucial in this research. The results confirm that MALL enables higher engagement and flexibility among learners while learning English vocabulary. Additionally, the results of this research confirm that MALL can effectively be used as a supplementary method for modern foreign language learning processes. Future research efforts should focus on different learning levels and productive learning of English vocabulary.
Keywords: Collaborative learning, educational integration, retention, self-regulation, personal practice, language skills, multifunctionality